Awareness, knowledge and practicality of solat among the in-ward patient: A preliminary study - Mohamed, Abdul Hadi; Abdullah, Nor Zamzila; Che Ahmad, Aminudin; Che Abdullah, Shahrin Tarmizi; Mohd Amin, Azril; Awang, Mohd Shukrimi; Abd. Wahab, Noraziana; Awang, Mohamed Saufi (The Faculty of Medicine, International Islamic University Malaysia, 2013)
Islam is a comprehensive way of life which is built on five pillars in which solat (prayer) is one of them. It is compulsory for Muslims to perform the five times a day solat at prescribed times. Islam has however given flexibility for ill patients to perform solat according to their ability. The aim of this study was to find out whether in-ward patients performed the five-time a day solat and the reasons for not performing if they abandoned their solat . A set of questionnaire was designed to look into their knowledge, attitude and practice. The questionnaires were distributed to hospitalized Muslim patients from selected hospitals in Malaysia namely Queen Elizabeth Hospital (Sabah), Sultanah Nur Zahirah Hospital (Terengganu), Raja Perempuan Zainab II Hospital (Kelantan), Batu Pahat Hospital (Johor) and Tengku Ampuan Afzan Hospital (Pahang). Out of 109 patients who participated in this study, only 74 (67.9%) of them performed the prescribed solat while 35 (32.1%) neglected their solat during their ward stay. Two of the patients who neglected their solat admitted that they had never learned about it. Four of them knew but never practiced even when they were not hospitalized, while 29 patients only abandoned their solat while in the hospital. The reasons given were poor knowledge on performing solat under sick conditions, limitations due to pain, poor mobility and hospital support. Most of the patients (83.5%) felt guilty for not performing the prescribed solat. Lack of knowledge and awareness of the importance of solat were among the factors that hindered patients from performing solat during admissions. Problems related to limited mobility due to pain and poor hospital support were also contributing factors. Therefore team efforts involving government and non-governmental organization, hospital administrators and staff as well as medical and nursing students are needed to improve the situation. The knowledge and awareness may be brought about through distribution of leaflets and educational sessions. Improvement of hospital facilities should also be made in-line with ibadah friendly hospital.